Odpowiedzi

2009-12-16T18:26:39+01:00
X-2y=-4
0,5x+y=2

x=-4+2y
2+y+y=2

x=-4+2y
y=0

x=-4
y=0
2009-12-16T18:28:03+01:00
X-2y = -4 | +2y
0,5x+y = 2

x = -4 + 2y
0,5x + y = 2

x = -4 + 2y
0,5(-4 + 2y) + y = 2

x = -4 + 2y
-2 + y + y = 2

x = -4 + 2y
-2 + 2y = 2 | + 2

x = -4 + 2y
2y = 4 | : 2

x = -4 + 2y
y = 2

x = -4 + 2 × 2
y = 2

x = 0
y = 2
1 5 1
2009-12-16T18:30:20+01:00
X-2y=-4 |+ 2y
0,5x+y=2
x=-4+2y
0,5(-4+2y)+y=2
x=-4+2y
-2+y+y=2|+2
x=-4+2y
2y=4|/2
x=-4+2y
y=2
x=-4+2*2
y=2
x=0
y=2
sprawdzenie
0,5*0+2=2
2=2
0-4=-4
-4=-4